2002
DOI: 10.1038/sj/jim/7000249
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-dependent autoaggregation of Pseudomonas putida CP1 during the degradation of mono-chlorophenols and phenol

Abstract: A bacterium, CP1, identified as Pseudomonas putida strain, was investigated for its ability to grow on and degrade mono-chlorophenols and phenols as sole carbon sources in aerobic shaking batch culture. The organism degraded up to 1.56 mM 2- and 3-chlorophenol, 2.34 mM 4-chlorophenol and 8.5 mM phenol using an ortho-cleavage pathway. P. putida CP1, acclimated to degrade 2-chlorophenol, was capable of 3-chlorocatechol degradation, while P. putida, acclimated to 4-chlorophenol degradation, degraded 4-chlorocatec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…The upregulation of the glucan-binding protein GbpC in conjunction with the increase in glucan may be the basis for enhanced DDAG. Similar autoaggregating phenotypes have been associated with the promotion of adhesion and biofilm formation (8) or alternatively may be associated with stress whereby the organisms attempt to protect themselves from adverse environmental conditions (10,29).…”
Section: Discussionmentioning
confidence: 99%
“…The upregulation of the glucan-binding protein GbpC in conjunction with the increase in glucan may be the basis for enhanced DDAG. Similar autoaggregating phenotypes have been associated with the promotion of adhesion and biofilm formation (8) or alternatively may be associated with stress whereby the organisms attempt to protect themselves from adverse environmental conditions (10,29).…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, auto-aggregation of bacteria can be induced and even become a permanent feature. Pseudomonas putida CP1 exhibits auto-aggregation during the degradation of monochlorophenols and phenol, and it has been shown that this is a response to the toxicity of the added substrates (Farrell & Quilty, 2002). Bossier et al (2000) observed that after inoculation of the non-aggregative Ralstonia eutropha-like strain AE815 into activated sludge, reisolation on selective medium yielded mutant strain A3, which was characterized by autoaggregative behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…A number of theories have been proposed for the autoaggregation of micro-organisms, including factors such as substrate gradients, slow growth of the organism, physical/ chemical stress, and predation (Farrell & Quilty, 2002). In some cases, auto-aggregation of bacteria can be induced and even become a permanent feature.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical stress by toxic compounds is one factor among the possible triggers for active bacterial aggregation. For example, Pseudomonas putida strain CP1 forms aggregates during degradation of chlorophenols (Farrell and Quilty 2002), and Comamonas testosteroni strain A20 acquires the ability to co-aggregate with yeast cells in response to hydrogen peroxide (Bossier and Verstraete 1996a). Formation of aggregates as a protection mechanism appears to be an attractive concept because bacteria in biofilms are known to be more resistant against biocides than suspended cells (Lewis 2001;Gilbert et al 2002).…”
Section: Introductionmentioning
confidence: 99%